Leaders’ Windows of Tolerance for Affect Arousal—and Their Effects on Political Decision-making During COVID-19 - Larsen, Kelsey L.; Stanley, Elizabeth A. (Frontiers in Psychology, 2021)
The recent ‘affect revolution’ in strategic decision-making research has placed greater emphasis on the role of stress and emotions in decision-making, with new theorizing to highlight how leader decisions often differ from rational choice expectations. However, while existing theories add to our understanding of the interplay between affect and cognition, they have not yet explained why affect drives decisions in some situations and not others. Undertheorized connections between leaders’ neurobiological windows of tolerance to affect arousal and their self-regulatory capacity—their capacity to regulate stress and emotions so that these phenomena do not drive resulting decisions—may hold the key to explaining this variation in affect’s influence on decision-making. Furthermore, this article considers how leaders’ windows of tolerance have unique ripple effects in their social environments, thereby affecting their groups’ collective window of tolerance. While regulated leaders can convey a calming and creative influence in their organizations that helps the group access strategic decision-making, dysregulated leaders are likely to convey stress and emotion contagion—which may erode the group’s ability to cooperate, adapt, and learn. It illustrates this argument using evidence from the upper echelons of governmental decision-making, comparing New Zealand Prime Minister Jacinda Ardern’s and US President Donald Trump’s responses to the coronavirus pandemic in their respective nations. It concludes by offering hypotheses for testing the argument in future empirical research.